Pengaruh Citra Merek, Harga, Online Customer Review Terhadap Keputusan Pembelian Produk Sepatu Converse Di Shopee : (Studi Kasus Mahasiswa Universitas Bhayangkara Fakultas Ekonomi Dan Bisnis Angkatan 2020) - Ivan Ardiansyah; Murti Wijayanti; Dody Kurniawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this research is to find out whether Brand Image, Price, and Online Customer Reviews influence purchasing decisions. This research is quantitative research using Purposive Sampling calculations with the Slovin formula. The population in this study were students at Bhayangkara University, Greater Jakarta, Class of 2020. The number of samples used in this research was 154 respondents. Based on the results of research in the Partial Test (t test), the Brand Image Variable (X1) has a positive and significant influence on Purchasing Decisions with a t value of 2.655 > 1.97580 (t table) with a significance value of 0.009 < 0.05. The Price variable (X2) has a positive and significant influence on purchasing decisions with a value (tcount) 2.733 > (ttable) 1.97580 with a significant value of 0.007 < 0.05. The Online Customer Review variable (X3) has a significant influence on purchasing decisions with a value (tcount) 4.071 > (ttable) 1.97580 with a significant value of 0.000 < 0.05. Furthermore, in the Simultaneous Test (f test) the Brand Image, Price and Online Customer Review variables simultaneously have a positive and significant effect on the Purchasing Decision variable with an fcount value of 13.817 with a significance value of 0.000 and a ftable value of 2.66. The fcount value is greater than the ftable value and the significance value is 0.000 < 0.05. then the Coefficient of Determination Test (Adjust R2) resulted in the correlation between the variables Brand Image (X1), Price (X2), Online Customer Review (X3) on Purchasing Decisions (Y) of 20.1%.